The Role of Modern Pedagogical Technologies in the Development of the Science of Pedagogy (Journal of Pedagogical Inventions and Practices, 2023)
In today's pedagogy, technology has a special place in changing the way education is delivered and experienced. It revolutionized teaching methods, expanded learning opportunities, and opened up new opportunities for both educators and students. Here we explore the different ways technology is impacting education.